Graphene coated fabrics by ultrasonic spray coating for wearable electronics and smart textiles. (15th December 2020) - Sreeja Sadanandan, Kavya; Bacon, Agnes; Shin, Dong-Wook; Alkhalifa, Saad F R; Russo, Saverio; Craciun, Monica F; Neves, Ana I S
Abstract: The seamless incorporation of electronics in textiles have the potential to enable various applications ranging from sensors for the internet of things to personalised medicine and human-machine interfacing. Graphene electronic textiles are a current focus for the research community due to the exceptional electrical and optical properties combined with the high flexibility of this material, which makes it the most effective strategy to achieve ultimate mechanical robustness of electronic devices for textile integrated electronics. An efficient way to create electronic textiles is to fabricate devices directly on the fabric. This can be done by coating the textile fabric with graphene to make it conductive. Here we discuss successful and efficient methods for coating graphene nanoplatelets on textile substrates of nylon, polyester and meta-aramid using ultrasonic spray coating technique. These coatings are characterised by scanning electron microscopy, contact angle and electrical conductivity measurements in order to identify the optimal textile electrode. Our study provides the foundation for the large-area fabrication of graphene electronic textiles.